Differences in communicative competence in English language achieved by students taking English majors and those training to be bilingual executive secretaries: seeking reasons - Marinho, Railuci de Góes Moreno (2006)
This article seeks to investigate the level of communicative competence achieved by students taking Portuguese & English majors and those reading for BAs as Bilingual Secretariat at the Catholic University of Goiás(UCG) and to explain the differences observed. Since similar methods are used in the first four semesters for the two courses, the fifth term was chosen for student self-assessment, testing of the various competences and the holding of interviews, in the first stage of the research. In the second stage, the levels of competence among students were tested for students in all five semesters, classes were observed, and some students were interviewed, as were two teachers. Analysis of the results obtained suggests a need to undertake further research to check critical points in the teaching of English language for both degree courses.